Dangdut Koplo Las Vegas Pati : The Analysis of Song form Structure and Creativity of Process - Tandho, Bandhu; Rohidi, Tjetjep Rohendi (Catharsis, 2018)
Dangdut Koplo is part of dangdut music genre that grows due to the influence of culture and music industry. The purpose of the study is to gain the understanding about the song form structure and process creativity of Dangdut Koplo Ã¢â‚¬Å“Las VegasÃ¢â‚¬Â performance in Pati. This research used interdisciplinary approach in the fields of music and psychology with qualitative descriptive analytic method. The technique of data collection was through observation, interview, and documentation. The data validity technique used triangulation of source and theory triangulation, while data analysis technique was done by textual analysis,i.e., musical analysis and contextual with interactive data analysis model using the process of data reduction, data presentation, and draw conclusion/verification. Research results show that the song form structure of Dangdut Koplo Ã¢â‚¬Å“Las VegasÃ¢â‚¬Â has different in its musical composition form. The process creativity of Dangdut Koplo Ã¢â‚¬Å“Las VegasÃ¢â‚¬Â is through 4 (four) dimensions of definition based on its emphasis,they are person, process, product and press. The steps to express the process creativity are: (1) idea of process, (2) process, (3process goal and, (4) process results. Research results show that Dangdut Koplo group Ã¢â‚¬Å“Las VegasÃ¢â‚¬Â is a dangdut music group that occurs due to the enthusiastic from Pati societyÃ¢â‚¬â„¢swith Dangdut Koplo musical entertainment. The above reason makes this music group grows fast in Pati. The research results are hoped to become a reference for the next research by using another different method in order to explore more the creativity values from other groups of Dangdut Koplo.